Anesthetics and plants: no pain, no brain, and therefore no consciousness - Draguhn, Andreas; Mallatt, Jon M.; Robinson, David G. (Protoplasma, 2021)
Plants have a rich variety of interactions with their environment, including adaptive responses mediated by electrical signaling. This has prompted claims that information processing in plants is similar to that in animals and, hence, that plants are conscious, intelligent organisms. In several recent reports, the facts that general anesthetics cause plants to lose their sensory responses and behaviors have been taken as support for such beliefs. These lipophilic substances, however, alter multiple molecular, cellular, and systemic functions in almost every organism. In humans and other animals with complex brains, they eliminate the experience of pain and disrupt consciousness. The question therefore arises: do plants feel pain and have consciousness? In this review, we discuss what can be learned from the effects of anesthetics in plants. For this, we describe the mechanisms and structural prerequisites for pain sensations in animals and show that plants lack the neural anatomy and all behaviors that would indicate pain. By explaining the ubiquitous and diverse effects of anesthetics, we discuss whether these substances provide any empirical or logical evidence for “plant consciousness” and whether it makes sense to study the effects of anesthetics on plants for this purpose. In both cases, the answer is a resounding no.
Published online: 2 September 2020
Gesehen am 21.10.2021